If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 14s + 15k + -2s + -2k + -14 = 0 Reorder the terms: 7 + -14 + 15k + -2k + 14s + -2s = 0 Combine like terms: 7 + -14 = -7 -7 + 15k + -2k + 14s + -2s = 0 Combine like terms: 15k + -2k = 13k -7 + 13k + 14s + -2s = 0 Combine like terms: 14s + -2s = 12s -7 + 13k + 12s = 0 Solving -7 + 13k + 12s = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 13k + 7 + 12s = 0 + 7 Reorder the terms: -7 + 7 + 13k + 12s = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 13k + 12s = 0 + 7 13k + 12s = 0 + 7 Combine like terms: 0 + 7 = 7 13k + 12s = 7 Add '-12s' to each side of the equation. 13k + 12s + -12s = 7 + -12s Combine like terms: 12s + -12s = 0 13k + 0 = 7 + -12s 13k = 7 + -12s Divide each side by '13'. k = 0.5384615385 + -0.9230769231s Simplifying k = 0.5384615385 + -0.9230769231s
| 5z-20z=25 | | 7(2l+10)=224 | | 0.03x^2-0.6x+10=0 | | 15x-18x= | | 4(3x-7)-(2x-6)=68 | | 2x^2+9x-66=0 | | -25-1/5=3/5n | | 4(3x-7)-(2x-60)=68 | | 0=(-140T)+5T^2 | | 0.19=1-x | | x^4-20x^2+25=9x^2-75 | | 5x-22=3x-26 | | 7(3G+4)-2g=5(2g-4)+3 | | 5x-22=3x-36 | | 2x^3-65x-75=0 | | [1/4(1-5)] | | 5k+2=-8 | | r+5.73=10 | | 1/2x-7=1/3(x-12) | | 5d-6a+7d+3a-2+8a+7= | | -(2x-1)+x=7 | | 10.5=-1.5-1.5x | | X=102+18x | | 5y+13=1-3 | | -5y+9=-8y-6 | | 12x+9=6x-15 | | 33=2v+13 | | F=MGH | | X-88=9(2x+3)-13 | | 5x^3-4x^2+8=0 | | 4x^2-15x+18=-2x+8 | | 5ad-6a+7d+3a-2+8a+7= |